Phytochemical Screening and Antimicrobial Activity of Desmodium ramosissimum - Toyigbénan, Badé Farid; Dah-Nouvlessounon, Durand; SINA, HAZIZ; Nanoukon, chimène; BABA-MOUSSA, FARID A. KADER (My University, 2020)
Microbial infections threaten the health of the Beninese population. Objec- tives: To identify bioactive phytochemical groups and evaluate the antimi- crobial activity of Desmodium ramosissimum used in traditional medicine in Benin against microbial infections. Methodology & Results: The classic reactions in solution helped highlight alkaloids, anthocyanins, flavonoids, quinones, saponins, steroids, tannins, terpenoids, mucilage, Coumarin, re- ducing compounds, anthracene, glycosides. The antibacterial activity was evaluated by extracts dilution’s method (ethanol extracts, methanol extracts and hexane extracts). The methanol extract inhibited the growth of all tested germs, with a significant effect on E. coli and S. aureus strains whose MIC values are equal to 1.25 mg/ml. On the contrary, this extract has a low activity on P. vulgaris strain with a MIC of 10 mg/ml. The ethanol extract also inhi- bited the growth of all the tested strains, but with more intense activity than the methanol extract. The strains of C. albicans and S. oralis were more sensi- tive to the extract with 0.625 mg/ml for MIC, while S. aureus and P. vulgaris were less sensitive (MIC = 5 mg/ml). The residual ethanol extract exerted in- hibition on all microorganisms at a concentration of 20 mg/ml, except the strain of E. foecalis that was resistant. Conclusion & Applications: This study shows that besides its food virtues of this plant, there are antibacterial and antifungal properties.
Keywords: Desmodium; Benin; Extracts; Antimicrobial; Screening